(untitled) (Journal of Education and Development, 2019)
Shall we flip for a betterment? Flipped learning is a common method that is widely used in secondary and tertiary education. So, how about primary education? Many would question whether this method could be utilised effectively in a primary school ESL classroom. Undoubtedly, this is indeed one of the main issues that worried the authorities. Due to the lack of empirical studies, the Malaysian society was not confident to use flipped learning in primary school. So, this study would therefore explore the acceptance level of flipped learning approach among primary school students, to check out the which construct affects the acceptance level the most as well as to find out the factors that influence their choice. This research was hoped to provide insights into attracting more educators to try out flipped learning in ESL classroom. In this study, it used a mixed-method design where quantitative data from survey and responses from group interviews were used to measure the outcomes. Initially, all Year 6 students from a primary school in Malaysia were chosen to experience flipped learning. Then 215 students were chosen as survey participants while another 15 among them were selected for focus group interviews. It had found out that effort expectancy was the major contributor towards the acceptance level and there are three factors that affect the behavioral intention,namely, clear interface, time efficacy and user friendly. This positive result was hoped to attract more educators to flip for a betterment.